Cover crop cultivars and species differ in root traits potentially impacting their selection for ecosystem services - Kong M. Wong; Marcus Griffiths; Amelia Moran; Andrea Johnston; Alexander E. Liu; Mitchell A. Sellers; Christopher N. Topp (Plant and Soil, 2024)
Background and aims Cover crops have the potential to aid in adapting agricultural systems to climate change impacts through their ecosystem services, such as preventing soil erosion, remediating soil structure, and storing carbon belowground. Though roots are integral to these processes, there is a lack of cover crop root trait data. This study aims to characterize rooting behavior of several commercially available cover crops and assess how differences in root system architecture potentially impact their selection for ecosystem services. Methods Twenty-two cover crop cultivars across the grass, legume, and brassica families were grown in O’Fallon, Missouri, USA. Canopy cover was monitored throughout the growing season. Shoot and root biomass samples were collected and analyzed. Results Cereal rye and winter triticale were the most winter hardy cultivars and provided the highest percent canopy cover. Cereal rye and winter triticale also generated the highest amount of shoot and root biomass among treatments but diverged in their root system architectures. Winter triticale forms coarser roots and exhibited deeper rooting, which may be better suited for carbon sequestration. Rapeseed and Siberian kale have favorable C:N ratios for nutrient recycling, but rapeseed may invest more into lateral root formation and have a higher potential to “catch” excess nutrients. Conclusion Selection of cover crops for ecosystem services should account for root system architecture and their suitability for these ecosystem services. Differences in root traits among cultivars within the same family highlight the potential to breed cover crop root system architecture to further enhance ecosystem service efficacy.

Transformation of rice with long DNA-segments consisting of random genomic DNA or centromere-specific DNA - Bao H. Phan; Weiwei Jin; Christopher N. Topp; Cathy X. Zhong; Jiming Jiang; R. Kelly Dawe; Wayne A. Parrott (Transgenic Research, 2007)

Integration of the Gene for Carboxin Resistance Does Not Impact the Ustilago maydis -Maize Interaction - Christopher N. Topp; José Ruiz-Herrera; Alfredo D. Martínez-Espinoza; Scott E. Gold (Current Microbiology, 2002)